2017
DOI: 10.1007/s12035-017-0663-7
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Attenuates High-Fat Diet-Induced Cognitive Impairment via Metabolic Regulation and Anti-inflammation of Obese Mice

Abstract: Accumulating studies suggest that overnutrition-associated obesity may lead to development of type 2 diabetes mellitus and metabolic syndromes (MetS). MetS and its components are important risk factors of mild cognitive impairment, age-related cognitive decline, vascular dementia, and Alzheimer’s disease. It has been recently proposed that development of a disease-course modification strategy toward early and effective risk factor management would be clinically significant in reducing the risk of metabolic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 81 publications
7
75
0
Order By: Relevance
“…Previous study showed that peripherally derived FGF-21 leaked into the injured brain and facilitate remyelination in a mouse model of lysophosphatidylcholine-induced demyelination [44]. In addition, subcutaneously injection of recombinant human FGF-21 improved cognitive function via attenuating insulin resistance and inflammatory response in an obese mouse model [45]. Whether elevated expression of FGF-21 following our resistant training also contributed to the benefits seen in the brain should be further determined.…”
Section: Discussionmentioning
confidence: 97%
“…Previous study showed that peripherally derived FGF-21 leaked into the injured brain and facilitate remyelination in a mouse model of lysophosphatidylcholine-induced demyelination [44]. In addition, subcutaneously injection of recombinant human FGF-21 improved cognitive function via attenuating insulin resistance and inflammatory response in an obese mouse model [45]. Whether elevated expression of FGF-21 following our resistant training also contributed to the benefits seen in the brain should be further determined.…”
Section: Discussionmentioning
confidence: 97%
“…In a high‐fat, diet‐induced obese mouse model, recombinant human FGF21, which is used to treat obesity and diabetes, can improve cognitive dysfunction, restore synaptic plasticity, and ameliorate anxiety‐like behavior (63, 64). Along the same lines, our data showed that WD‐induced inflammatory signaling was accompanied by reduced Fgf21 gene expression in microglia and brain, as well as other organs.…”
Section: Discussionmentioning
confidence: 99%
“…mice We next investigated if mechanism underlying the reduction of Aβ load in the brain of APP/PS1 mice could be partially mediated by the molecular regulation of PPARγ levels, which play a master role in the regulation of the neuroinflammatory processes in AD ( Fig 5). Indeed, previous research has demonstrated that P reduces Aβ deposition in association with Akt/GSK3β activation by increasing the levels of insulin-degrading enzyme (IDE) and PPARγ expression [39]. For that reasons, in the current study, the downstream effect of treatment on PPARγ was investigated.…”
Section: Effects Of the Treatments On The Molecular Regulation Of Ppamentioning
confidence: 98%